Clinical and Genetic Study of X-Linked Juvenile Retinoschisis in the Czech Population - Kousal, Bohdan; Hlavata, Lucia; Vlaskova, Hana; Dvorakova, Lenka; Brichova, Michaela; Dubska, Zora; Langrova, Hana; Vincent, Andrea L; Dudakova, Lubica; Liskova, Petra (Genes, 2021)
The aim of this study was to identify RS1 pathogenic variants in Czech patients with X-linked retinoschisis (XLRS) and to describe the associated phenotypes, including natural history, in some cases. Twenty-one affected males from 17 families were included. The coding region of RS1 was directly sequenced and segregation of the identified mutations was performed in available family members. In total, 12 disease-causing variants within RS1 were identified; of these c.20del, c.275G>A, c.[375_379del; 386A>T], c.539C>A and c.575_576insT were novel, all predicted to be null alleles. The c.539C>A mutation occurred de novo. Three patients (aged 8, 11 and 19 years) were misdiagnosed as having intermediate uveitis and treated with systemic steroids. Repeat spectral domain optical coherence tomography examinations in four eyes documented the transition from cystoid macular lesions to macular atrophy in the fourth decade of life. Four individuals were treated with topical dorzolamide and in two of them, complete resolution of the cystic macular lesions bilaterally was achieved, while one patient was noncompliant. Rebound phenomenon after discontinuation of dorzolamide for 7 days was documented in one case. Misdiagnosis of XLRS for uveitis is not uncommon; therefore, identification of disease-causing variants is of considerable benefit to the affected individuals.
Keywords: Infant; Adolescent; sulfonamidy; Antihypertensive Agents; rodokmen; optická koherentní tomografie; retinoschisis; lidé; oční proteiny; Humans; Child; Mutation; antihypertenziva; Tomography, Optical Coherence; Gene Frequency; frekvence genu; Child, Preschool; Thiophenes; Czech Republic; Eye Proteins; kojenec; thiofeny; Sulfonamides; dítě; Česká republika; mladiství; mutace; Retinoschisis; Pedigree; předškolní dítě